Identification, characterization and quantification of mine wastewater loading in the surface water of Bued River - Alfonso, Shiela Marie P.; Leones, Jade Marjorie S.
Aside from the contribution to the economic development in our country, mining industry has also brought environmental problems due to improper mine waste disposal. One of which is the pollution of nearby bodies of water. From previous studies, Bued River, located in Tuba, Benguet, was found to be contaminated with heavy metals disposed by mining companies near the river. For this study, the aim was to determine the mine wastewater loading in the downstream surface of Bued River. This could be achieved by identifying the small-scale mining industries near Bued River and its tributaries, identifying the physical and chemical characteristics of mine wastewater, and quantifying the mine wastewater loading discharged to Bued River. Ten small-scale mining sites were identified and mapped in Camp 3, Camp 6, and Barangay Kias. Wastewater and sediment samples from these sites were collected and were physically and chemically characterized. Using Horiba, pH and temperature were measured in-situ, while total suspended and dissolved solids were measured in the lab. Metalyser HM3000, developed by Trace20, was used to measure heavy metal concentrations. Based on the results, the samples were found to contain Mercury, .Arsenic and Lead. Arsenic and Lead concentrations of all wastewater samples passed both the Department of Environment and Natural Resources Administrative Order 35 and Philippine Regulations on Sanitation and Wastewater Systems. In terms of Mercury, six out of 12 wastewater samples passed the former, while only two samples, from Barangay Kias, had values acceptable by the latter. For the sediment samples, four standards were used for comparison: National Oceanographic and Atmospheric Administration (NOAA) Guidelines, Florida Department of Environmental Protection (FDEP) Guidelines, Ontario Ministry of Environment Guidelines and the Interim Sediment Quality Guidelines (ISQG). All sediment samples had heavy metal concentrations lower than the four standards. Wastewater loading was quantified through discharge measurement at a given time. Relative to others, sample from J. Mill 3 had higher heavy metal concentrations loaded to the river. However, these concentrations contributed by the identified mining sites to Liwliw Creek, a tributary to Bued River, to which most of the sampling sites drain, are of less significance based on the amount of heavy metals quantified in Liwliw creek as compared to some other sampling points along the river.